2020
DOI: 10.1016/j.celrep.2020.108152
|View full text |Cite
|
Sign up to set email alerts
|

Visual Sequences Drive Experience-Dependent Plasticity in Mouse Anterior Cingulate Cortex

Abstract: SUMMARY Mechanisms of experience-dependent plasticity have been well characterized in mouse primary visual cortex (V1), including a form of potentiation driven by repeated presentations of a familiar visual sequence (“sequence plasticity”). The prefrontal anterior cingulate cortex (ACC) responds to visual stimuli, yet little is known about if and how visual experience modifies ACC circuits. We find that mouse ACC exhibits sequence plasticity, but in contrast to V1, the plasticity expresses as a chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 96 publications
(167 reference statements)
1
22
0
Order By: Relevance
“…Consistent with the idea that hippocampus has a special role in binding relational properties in widely distributed neocortical circuits, recent work has shown that encoding of visual sequences occurs broadly, extending beyond V1 to include anterior cingulate cortex (ACC) (49). We note, however, that although ACC is one of the major intermediaries connecting hippocampus with V1, unlike hippocampus, it is not required for sequence-specific potentiation of VEPs in V1 (49).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with the idea that hippocampus has a special role in binding relational properties in widely distributed neocortical circuits, recent work has shown that encoding of visual sequences occurs broadly, extending beyond V1 to include anterior cingulate cortex (ACC) (49). We note, however, that although ACC is one of the major intermediaries connecting hippocampus with V1, unlike hippocampus, it is not required for sequence-specific potentiation of VEPs in V1 (49).…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, anticipatory response modulation within a familiar sequence inherently involves pattern completion (the ability to retrieve a complete record of sensory experience when provided a subset of the original cues), which has been attributed to autoassociative network properties conferred by the anatomical connectivity of the hippocampus (33,47,48). Consistent with the idea that hippocampus has a special role in binding relational properties in widely distributed neocortical circuits, recent work has shown that encoding of visual sequences occurs broadly, extending beyond V1 to include anterior cingulate cortex (ACC) (49). We note, however, that although ACC is one of the major intermediaries connecting hippocampus with V1, unlike hippocampus, it is not required for sequence-specific potentiation of VEPs in V1 (49).…”
Section: Discussionmentioning
confidence: 98%
“…In the context of long-loop modulation, an interesting bridge between hippocampus and V1 is the anterior cingulate cortex, [54][55][56] which was recently shown to express sequence-specific VEP potentiation. 57 However, genetic and pharmacogenetic manipulations showed that anterior cingulate cortex is not obligatory for either induction or expression of sequence-specific potentiation in V1. 57 The question remains as to how the hippocampus might be involved in sequence-specific plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…57 However, genetic and pharmacogenetic manipulations showed that anterior cingulate cortex is not obligatory for either induction or expression of sequence-specific potentiation in V1. 57 The question remains as to how the hippocampus might be involved in sequence-specific plasticity. A clue might be the additional requirement of cholinergic transmission in V1.…”
Section: Discussionmentioning
confidence: 99%
“…Insights gained from V1 may apply broadly to other regions as well (Douglas & Martin, 2004; Douglas, Martin, & Whitteridge, 1989; Edelman & Mountcastle, 1978; Hawkins & Ahmad, 2016), making this an experimentally accessible area in which to study the cortical basis of predictive processing. In the present study, we investigated predictive processing in the context of a specific form of sequence learning previously described as in V1 (Finnie et al, 2021; Gavornik & Bear, 2014) and anterior cingulate cortex (ACC) (Sidorov et al, 2020). Specifically, we passively exposed mice to rapidly-flashed sequences of sinusoidal gratings, whose spatiotemporal structure differs dramatically from the approximate 1/ f spectrum of their natural environment (Carandini et al, 2005; Ocko, Lindsey, Ganguli, & Deny, 2018; Olshausen & Field, 1997).…”
Section: Introductionmentioning
confidence: 99%